Preparation method of silicon solar cell with coplanar electrode
By adopting coplanar electrode and pulsed laser doping technology in silicon solar cells, the shortcomings of traditional electrode design and doping methods are solved, efficient absorption and low power consumption of long-wave infrared light are achieved, and photoelectric conversion efficiency is improved.
Patent Information
- Application Number
- CN202510723862.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-01
- Publication Date
- 2025-09-02
AI Technical Summary
Traditional silicon solar cells cause photogenerated carriers to be recombined before being received in electrode design, and traditional doping technology is difficult to achieve high concentration doping and depth controllable, limiting the photogenerated carrier transport path and absorption efficiency.
Using coplanar electrode structure and pulsed laser doping technology, by forming a sixGe1-x absorbing layer with varying components and P and N-type electrodes on the silicon substrate, combined with laser irradiation Zn doping, the photogenerated carrier transport distance is reduced and high concentration doping is achieved, and ohmic contact resistance is optimized.
The absorption efficiency of solar cells to long-wave infrared light is improved, the photogenerated carrier transport distance and P-type ohmic contact resistance are reduced, the photoelectric conversion efficiency is improved, and the heating and power consumption are reduced.
Smart Images

Figure CN120583771A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing a silicon solar cell, and in particular to a method for preparing a silicon solar cell with coplanar electrodes. Background Art
[0002] Silicon, the second most abundant resource in the Earth's crust, is the foundation of modern semiconductor materials and devices. Monocrystalline silicon solar cells produce virtually no polluting emissions throughout their lifecycle. Silicon itself is non-toxic and harmless, providing long-term, stable, and reliable lifespan. They offer cost-effectiveness and efficiency that better meet the needs of large-scale commercial and household applications. Consequently, silicon solar cells are currently the most widely used type of solar cell.
[0003] Silicon has a band gap of 1.12 eV at room temperature and cannot absorb photons with wavelengths greater than 1100 nm. This means that its absorption of infrared wavelengths is very poor. This results in silicon-based photoelectric sensors being unable to respond to infrared light longer than 1100 nm, limiting their efficiency. Sunlight, on the other hand, contains an abundant amount of infrared light, accounting for approximately 48.3% of its total energy. Failure to effectively utilize this energy would result in significant waste.
[0004] When it comes to optimizing silicon solar cell electrodes, traditional designs require electrodes to be fabricated on both sides of the cell. However, this causes some photogenerated carriers to recombine before being received by the electrodes, which reduces the lifetime of the photogenerated carriers to a certain extent. The coplanar electrode used in the present invention only requires single-sided processing, that is, a P-type electrode metal is formed by vapor deposition on the sample surface, and then a finger-shaped electrode area is etched on the surface, and the etching depth is made to the silicon substrate, and then an N-type electrode metal is evaporated to form. The coplanar electrode prepared in this way can effectively reduce the transport path of photogenerated carriers and improve the absorption efficiency of the battery. In addition, there are two key factors for the formation of a good ohmic condition for the electrode: the interface barrier between the metal and the semiconductor needs to be sufficiently low, and the semiconductor contact area needs to be doped with a high concentration. Traditional semiconductor doping methods mainly include epitaxial doping and ion implantation. The doping concentration of epitaxial doping is easily limited, and the doping impurities are easily migrated at high temperatures of the epitaxial layer, resulting in uncontrollable doping depth; ion implantation doping can achieve controllable doping concentration and depth, but its doping area is small, the efficiency is low, the cost is high, and it is easy to destroy the material lattice, causing material damage. Compared with traditional doping technologies such as ion implantation and epitaxial doping, the pulsed laser doping used in the present invention has the advantages of precise control of doping concentration and depth, and no material damage. It can achieve high-concentration P-type doping of the surface Si covering layer, which is beneficial to reducing the P-type ohmic contact resistance. Summary of the Invention
[0005] The purpose of the present invention is to provide a method for preparing a silicon solar cell with coplanar electrodes, which greatly improves the absorption efficiency by adopting an absorption layer with a variable composition, reduces the P-type series resistance by laser irradiation Zn doping, and finally improves the photogenerated carrier transport path by using the coplanar electrode method, effectively improving the solar spectrum absorption efficiency.
[0006] To achieve the above object, the present invention adopts the following technical solutions: A method for preparing a silicon solar cell with coplanar electrodes comprises the following steps: 1) First, clean the N-type silicon substrate with acetone, methanol, isopropanol, and deionized water respectively, then immerse it in hydrofluoric acid to remove the oxide layer on the surface of the silicon substrate, rinse it with deionized water, and blow dry it with nitrogen; 2) epitaxially growing an N-type silicon buffer layer on the N-type silicon substrate pretreated in step 1) using metal organic chemical vapor deposition (MOCVD) technology; 3) Using MOCVD technology, three layers of P-type Si with decreasing Si content are sequentially grown on the N-type silicon buffer layer formed in step 2) x Ge 1-x Absorbent layer; 4) epitaxially growing a P-type Si capping layer on the absorption layer formed in step 3) using MOCVD technology; 5) Vacuum evaporation is used to deposit a Zn metal thin film on the covering layer formed in step 4); 6) irradiating the metal surface of the sample obtained in step 5) with a pulsed laser to achieve P-type heavy doping, then removing the residual metal on the sample surface with hydrochloric acid etching, followed by cleaning and drying; 7) Sputtering a Ti / Al metal layer on the surface of the sample dried in step 6) to form a P-type metal electrode; 8) The finger-shaped electrode area is prepared by photolithography and development, and then the area is etched to the substrate by ICP. A Ti / Al metal layer is then evaporated to form an N-type metal electrode in the area. The P-type metal electrode and the N-type metal electrode are then annealed in a nitrogen atmosphere to achieve ohmic contact, thereby completing the preparation of the silicon solar cell.
[0007] Furthermore, the N-type silicon substrate in step 1) is a phosphorus-doped silicon wafer with a thickness of 300 μm and a doping concentration of 10 18 cm -3 .
[0008] Furthermore, the thickness of the N-type silicon buffer layer formed in step 2) is 500 nm, wherein the phosphorus doping concentration is 10 18 cm -3 .
[0009] Furthermore, the thickness of the three layers of P-type SiGe absorption layers formed in step 3) are all 100 nm, and their material components along the growth direction are Si 0.8 Ge 0.2 、Si 0.6 Ge 0.4 、Si 0.4 Ge 0.6 .
[0010] Furthermore, the thickness of the P-type Si capping layer formed in step 4) is 500 nm, wherein the boron doping concentration is 2×10 18 cm -3 .
[0011] Furthermore, the thickness of the Zn metal film in step 5) is 50-300 nm.
[0012] Furthermore, the laser used in step 6) is a KrF excimer laser with a wavelength of 248 nm, which irradiates the metal surface of the sample for 1 to 6 seconds, has a single pulse energy of 100 to 600 mJ, and a pulse frequency of 10 to 30 Hz.
[0013] Furthermore, in step 6), deionized water is used for washing.
[0014] Furthermore, in the Ti / Al metal layer in step 7), the thickness of the Ti metal layer is 100 nm, and the thickness of the Al metal layer is 500 nm.
[0015] Furthermore, in the Ti / Al metal layer evaporated in step 8), the thickness of the Ti metal layer is 100 nm, and the thickness of the Al metal layer is 500 nm.
[0016] Furthermore, the annealing temperature in step 8) is 550° C. to 700° C., and the annealing time is 5 to 15 minutes.
[0017] The present invention adopts Si with varying composition x Ge 1-x The absorption layer forms a structure with different energy band gaps, effectively improving the absorption efficiency of long wavelengths that traditional silicon solar cells cannot absorb. The use of coplanar P and N electrodes reduces the transport distance of photogenerated carriers. Furthermore, the present invention utilizes pulsed laser doping, which can achieve high-concentration doping of the material, controllable doping depth and concentration, and zero material damage by regulating key parameters such as laser pulse energy, frequency, and duty cycle. This improves the P-type ohmic contact, effectively reducing the P-type series resistance, and thus effectively reducing heat generation and power consumption during cell operation.
[0018] The present invention has the following advantages: (1) The present invention constructs Si with different componentsx Ge 1-x The absorption layer has different band gap widths and absorbs sunlight wavelengths extending to longer infrared bands, achieving effective absorption of long waves that traditional silicon solar cells cannot absorb, and can effectively improve the absorption efficiency.
[0019] (2) The solar cell of the present invention adopts a coplanar electrode structure to reduce the transport distance of photogenerated carriers, which can effectively improve the photoelectric conversion efficiency.
[0020] (3) The present invention achieves nanometer-level P-type heavy doping (surface P-type doping concentration exceeds 10) by regulating the pulse time and pulse energy of KrF laser. 19 cm -3 ), effectively reducing the P-type ohmic contact resistance and device heating.
[0021] (4) The solar cell prepared by the present invention has the advantages of high absorption efficiency, low power consumption and low heat generation; it is easy to achieve low cost and industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the cross-section of the structure of the silicon solar cell of the present invention.
[0023] Figure 2 Schematic diagram of the structure of coplanar electrodes arranged on the silicon solar cell of the present invention. As can be seen in the figure, the P-type electrode and the N-type electrode are in an interdigitated shape.
[0024] Figure 3 This is a schematic diagram of the KrF laser irradiation system used in the present invention. The laser light emitted by the excimer laser is irradiated to the sample surface in the sample stage through a reflector. The sample stage adopts a two-dimensional mechanical motion platform to achieve automatic scanning. The sample stage is placed in a vacuum chamber to prevent oxidation. DETAILED DESCRIPTION
[0025] A method for preparing a silicon solar cell with coplanar electrodes comprises the following steps: 1) First, clean the N-type silicon substrate with acetone, methanol, isopropanol, and deionized water respectively, then immerse it in hydrofluoric acid to remove the oxide layer on the surface of the silicon substrate, rinse it with deionized water, and blow dry it with nitrogen; 2) Using metal organic chemical vapor deposition (MOCVD) technology, a 500nm thick N-type silicon buffer layer is epitaxially grown on the N-type silicon substrate pretreated in step 1) with a phosphorus doping concentration of 10 18 cm -3 ; 3) Using MOCVD technology, three 100nm thick P-type SiGe absorption layers are sequentially grown on the N-type silicon buffer layer formed in step 2). The specific composition is Si 0.8 Ge0.2 、Si 0.6 Ge 0.4 、Si 0.4 Ge 0.6 ; 4) MOCVD technology is used to grow a 500nm thick P-type Si cap layer on the absorption layer formed in step 3) with a boron doping concentration of 2×10 18 cm -3 ; 5) Vacuum evaporation is used to deposit a Zn metal thin film with a thickness of 50 to 300 nm on the covering layer formed in step 4); 6) irradiating the metal surface of the sample obtained in step 5) with a KrF excimer laser having a wavelength of 248 nm for 1 to 6 seconds, with a single pulse energy of 100 to 600 mJ and a pulse frequency of 10 to 30 Hz; then, removing the residual metal on the sample surface by etching with hydrochloric acid, followed by rinsing with deionized water and drying; 7) After drying in step 6), Ti / Al metal layers with thicknesses of 100 nm and 500 nm were sputtered on the surface of the sample to form P-type metal electrodes; 8) The finger-shaped electrode area is prepared by photolithography and development, and then the area is etched to the substrate using ICP. Ti / Al metal layers with thicknesses of 100nm and 500nm are evaporated to form an N-type metal electrode in this area. The N-type metal electrode is then annealed at 550℃~700℃ for 5~15min in a nitrogen atmosphere to achieve ohmic contact between the P-type metal electrode and the N-type metal electrode, thus completing the preparation of the silicon solar cell.
[0026] The N-type silicon substrate used is a phosphorus-doped silicon wafer with a thickness of 300 μm and a doping concentration of 10 18 cm -3 .
[0027] In order to make the contents of the present invention easier to understand, the technical solutions of the present invention are further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0028] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0029] The N-type silicon substrate used in the embodiment is a phosphorus-doped silicon wafer with a thickness of 300 μm and a doping concentration of 10 18 cm -3 .
[0030] Example 1 First, the N-type silicon substrate was cleaned with acetone, methanol, isopropanol, and deionized water, and then immersed in hydrofluoric acid to remove the naturally formed silicon dioxide layer. It was then rinsed with deionized water and dried with nitrogen. Then, a 500nm thick N-type phosphorus-doped Si buffer layer (doping concentration of 10) was epitaxially grown on the surface of the N-type silicon wafer using MOCVD technology. 18 cm -3 ), the three layers are 100nm thick and the components are Si 0.8 Ge 0.2 、Si 0.6 Ge 0.4 、Si 0.4 Ge 0.6 A P-type SiGe absorption layer, a 500nm thick P-type boron-doped Si cover layer (doping concentration of 2×10 18 cm -3 ). A 150nm thick Zn film was then vacuum-evaporated on the sample surface. The Zn / Si sample surface was then laser-doped using a 248nm KrF excimer laser in a vacuum environment (the laser pulse frequency was set at 15Hz and the single pulse energy was 300mJ). After irradiation for 3 seconds, the remaining Zn was removed using hydrochloric acid. The sample was then rinsed again with deionized water and dried with nitrogen. Titanium / aluminum (Ti / Al) metal layers with thicknesses of 100nm and 500nm were sputtered onto the prepared silicon sample surface as P-type electrodes. Finger-shaped electrode regions were then formed on the surface by photolithography. These regions were then etched to the substrate by ICP. Ti / Al metal layers with thicknesses of 100nm and 500nm were then evaporated as N-type electrodes. Annealing was performed at 500°C for 20 minutes in a nitrogen atmosphere to achieve ohmic contact between the P-type and N-type electrodes of the battery.
[0031] Example 2 First, the N-type silicon substrate was cleaned with acetone, methanol, isopropanol, and deionized water, and then immersed in hydrofluoric acid to remove the naturally formed silicon dioxide layer. It was then rinsed with deionized water and dried with nitrogen. Then, a 500nm thick N-type phosphorus-doped Si buffer layer (doping concentration of 10) was epitaxially grown on the surface of the N-type silicon wafer using MOCVD technology. 18 cm -3 ), the three layers are 100nm thick and the components are Si 0.8 Ge 0.2 、Si 0.6 Ge 0.4 、Si 0.4 Ge 0.6 A P-type SiGe absorption layer, a 500nm thick P-type boron-doped Si cover layer (doping concentration of 2×10 18 cm -3). Afterwards, a 250nm thick Zn film was vacuum-evaporated on the sample surface. The Zn / Si sample surface was then laser-irradiated and doped using a 248nm KrF excimer laser in a vacuum environment (the laser pulse frequency was set to 20Hz and the single pulse energy was 400mJ). After irradiation for 4 seconds, the residual Zn was removed using hydrochloric acid, and the sample was rinsed again with deionized water and dried with nitrogen. Titanium / aluminum (Ti / Al) metal layers with thicknesses of 100nm and 500nm were sputtered on the prepared silicon sample surface as P-type electrodes; finger-shaped electrode areas were then formed on the surface by photolithography, and then the areas were etched to the substrate by ICP. Ti / Al metal layers with thicknesses of 100nm and 500nm were then evaporated as N-type electrodes, and annealed at 650°C for 15 minutes in a nitrogen atmosphere to achieve ohmic contact between the P-type and N-type electrodes of the battery.
[0032] Example 3 First, the N-type silicon wafer was cleaned with acetone, methanol, isopropanol, and deionized water, and then immersed in hydrofluoric acid to remove the naturally formed silicon dioxide layer. It was then rinsed with deionized water and dried with nitrogen. Then, a 500nm thick N-type phosphorus-doped Si buffer layer (doping concentration of 10) was epitaxially grown on the surface of the N-type silicon wafer using MOCVD technology. 18 cm -3 ), the three layers are 100nm thick and the components are Si 0.8 Ge 0.2 、Si 0.6 Ge 0.4 、Si 0.4 Ge 0.6 A P-type SiGe absorption layer, a 500nm thick P-type boron-doped Si cover layer (doping concentration of 2×10 18 cm -3 ). Afterwards, a 300nm thick Zn film was vacuum-evaporated on the sample surface. The Zn / Si sample surface was then laser-irradiated and doped using a 248nm KrF excimer laser in a vacuum environment (the laser pulse frequency was set to 25Hz and the single pulse energy was 500mJ). After irradiation for 5 seconds, the residual Zn was removed using hydrochloric acid. The sample was then rinsed again with deionized water and dried with nitrogen. Titanium / aluminum (Ti / Al) metal layers with thicknesses of 100nm and 500nm were sputtered on the prepared silicon sample surface as P-type electrodes. Finger-shaped electrode areas were then formed on the surface by photolithography, and the areas were subsequently etched to the substrate by ICP. Ti / Al metal layers with thicknesses of 100nm and 500nm were then evaporated as N-type electrodes. The samples were annealed at 700°C for 10 minutes in a nitrogen atmosphere to achieve ohmic contact between the P-type and N-type electrodes of the battery.
[0033] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing a silicon solar cell with coplanar electrodes, characterized in that: The following steps are involved: 1) First, clean the N-type silicon substrate with acetone, methanol, isopropanol, and deionized water respectively, then immerse it in hydrofluoric acid to remove the oxide layer on the surface of the silicon substrate, rinse it with deionized water, and blow dry it with nitrogen; 2) epitaxially growing an N-type silicon buffer layer on the N-type silicon substrate pretreated in step 1) using metal organic chemical vapor deposition technology; 3) using metal organic chemical vapor deposition technology to sequentially grow three P-type SiGe absorption layers with decreasing Si content on the N-type silicon buffer layer formed in step 2); 4) epitaxially growing a P-type Si capping layer on the absorption layer formed in step 3) using metal organic chemical vapor deposition technology; 5) Vacuum evaporation is used to deposit a Zn metal thin film on the covering layer formed in step 4); 6) irradiating and doping the metal surface of the sample obtained in step 5) with a pulsed laser, then removing the residual metal on the sample surface with hydrochloric acid etching, followed by cleaning and drying; 7) Sputtering a Ti / Al metal layer on the surface of the sample dried in step 6) to form a P-type metal electrode; 8) The finger-shaped electrode area is prepared by photolithography and development, and then the area is etched to the substrate by ICP. A Ti / Al metal layer is then evaporated to form an N-type metal electrode in the area. The P-type metal electrode and the N-type metal electrode are then annealed in a nitrogen atmosphere to achieve ohmic contact, thereby completing the preparation of the silicon solar cell.
2. The preparation method according to claim 1, characterized in that The N-type silicon substrate in step 1) is a phosphorus-doped silicon wafer with a thickness of 300 μm and a doping concentration of 10 18 cm -3 .
3. The preparation method according to claim 1, characterized in that The thickness of the N-type silicon buffer layer formed in step 2) is 500 nm, and the phosphorus doping concentration is 10 18 cm -3 .
4. The preparation method according to claim 1, characterized in that The thickness of the three layers of P-type SiGe absorption layers formed in step 3) are all 100nm, and their material components along the growth direction are Si 0.8 Ge 0.2 、Si 0.6 Ge 0.4 、Si 0.4 Ge 0.6 .
5. The preparation method according to claim 1, characterized in that The thickness of the P-type Si capping layer formed in step 4) is 500 nm, and the boron doping concentration is 2×10 18 cm -3 .
6. The preparation method according to claim 1, characterized in that The thickness of the Zn metal film in step 5) is 50-300 nm.
7. The preparation method according to claim 1, characterized in that The laser used in step 6) is a KrF excimer laser with a wavelength of 248 nm. The irradiation time for the sample metal surface is 1 to 6 seconds, the single pulse energy of the laser is 100 to 600 mJ, and the pulse frequency is 10 to 30 Hz.
8. The preparation method according to claim 1, characterized in that In the Ti / Al metal layer in step 7), the thickness of the Ti metal layer is 100 nm, and the thickness of the Al metal layer is 500 nm.
9. The preparation method according to claim 1, characterized in that In the Ti / Al metal layer evaporated in step 8), the thickness of the Ti metal layer is 100 nm, and the thickness of the Al metal layer is 500 nm.
10. The preparation method according to claim 1, characterized in that The annealing temperature in step 8) is 550° C. to 700° C., and the annealing time is 5 to 15 minutes.